Duplication of the petrosphenoidal ligament: Report of a rare case with comments on clinical implications - Grzegorz Wysiadecki; Krzysztof Balawender; Joe Iwanaga; Edward Clarke; Anna Smędra; Michał Bonczar; Patryk Ostrowski; Andrzej Żytkowski (Elsevier, 2023)
Background: The petrosphenoidal ligament is the superior boundary of Dorello's canal and typically covers the abducens nerve and dorsal meningeal artery from above. The ligament is usually located within the inferomedial paraclival triangle and can be considered a crucial surgical landmark. Aim: This report describes a rare variant of PSL duplication and its topographical relationships. Case presentation: The duplicated petrosphenoidal ligament was found on the left side during the skull base dissection of a male cadaver. The first band of the duplicated PSL ran between the petrous apex and the dorsolateral border of the clivus. The accessory shorter band of the duplicated PSL was located below and slightly posterior to the previous one, between the edges of the inferior petrosal sinus origin. The abducens nerve, covered by a dural sleeve, ran together with the dorsal meningeal artery between these two PSL bands. Abducens nerve's dural sleeve was firmly attached to the upper surface of the accessory PSL band. On the contralateral side, the topographical relationships were typical with a single PSL. Conclusions: Topographical relationships between the petrosphenoidal ligament and surrounding structures can be highly variable, which should be considered during neurosurgical procedures in the petroclival region.